Economic comparison of tomato production on different type of insecticide application / Mohd Hafizan Mohd Yusoff - Mohd Yusoff, Mohd Hafizan (Faculty of Plantation and Agrotechnology, 2015)
In many agriculture practices, insecticide and pesticide are the only commonly use and effective means of controlling the disease, insect pest, and weeds. Therefore, the people that use insecticide or regularly come in contact with them must understand the relative toxicity, potential health effects, and preventive way to reduce the exposure to the chemical products that they use. This studies were conducted as an open field in Uitm Jasin Farm, Melaka in 2015 to evaluate and making economic comparison on the effect of different insecticide (selected chemical application) in to tomato production on yield and profitability of Solanum lycopersicom. The sample involved three treatments viz: Confidor 200 SL (IMIDACLOPRID), Sulfoxaflor 500 WG and untreated (water). The different yield may influenced the sales and increase the farmer's income. The better selected insecticide to the pest attack can give advantage to the farmers to reduce the cost of tomato production and gain more profit income. The purpose of this study is was to identify the most economically feasible according to the yield, income and benefit cost ratio of tomato production. This is important elements to the farmers to select the effective insecticide to increase their yield and profit while cost may been recovered by the sales of yield production.